Four seasons a Ming emperor and his grand secretaries in sixteenth-century China - Dardess, John W. 1937- (Lanham Rowman & Littlefield, 2016)
Richly researched and engagingly written, this important history of imperial China shows in fascinating detail how Emperor Jiajing and his grand secretaries governed. Drawing on a treasure trove of the grand secretaries' personal writings, John W. Dardess's narrative brings to life the inner workings of the largest polity on the face of the earth.
A young emperor shows his teeth -- Spring: Grand Secretary Zhang Fujing -- Summer: Grand Secretary Xia Yan -- Autumn: Grand Secretary Yan Song -- Winter: Grand Secretary Xu Jie -- Cast of principal characters -- Timeline.
Includes bibliographical references (pages 281-284) and index.
Keywords: Ming Shizong -- Emperor of China -- 1507-1567.; Ming Shizong -- Emperor of China -- 1507-1567 -- Friends and associates; Ming Shizong -- Emperor of China -- 1507-1567 -- Political and social views; China -- History -- Ming dynasty, 1368-1644.; China -- Politics and government -- 1368-1644.; Political leadership -- China -- History -- 16th century; Emperors -- China -- Biography; China -- Kings and rulers -- Biography; Public officers -- China -- Biography; China -- Officials and employees -- Biography